(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is devoted to defining the role of Pre-Columbian era in the formation of the phenomenon of Latin American literature. The author states that indigenous culture of America is a culture-factor and a source of identity construction paradigm shift in the culture of South America in the Modern Time.